Mengimaginasi Reka Bentuk Kostum dan Perhiasan Badan untuk Persembahan "Bermulanya Di Sini... Kedah Tua"! Re-imagining the Costume Design and Body Adornments for the Performance of "Bermulanya Di Sini…Kedah Tua"! - Carren Hong Kim Lan; Nur Hilyati Ramli; Mumtaz Begum Aboo Backer; Muhizam Mustafa; Mohd Najib Abdullah Sani (Wacana Seni Journal of Arts Discourse, 2019)
The most important function of costume design in theatrical play is to aid the performers tell the story in a "make-believe" manner. Costumes help identify the role and responsibility of the performers through the understanding of character's needs and contributions to the development of the story. This paper presents a critical review of the costumes and body adornments used for the performance of "Bermulanya Di Sini... Kedah Tua". The materials and design were carefully selected based on the information gathered from preliminary literature review and archaeological excavations at the Lembah Bujang site. Given Kedah Tua's historical flourishing metal industry, the wardrobe team was selective in choosing costumes and ornaments which semiotically showed cultural and historical significance to the elements of metal and nature. Additionally, the choice of colour scheme, costumes and body adornments were informed by the documented accounts of the community's different social hierarchy during the 5th CE through a unique array of custom lifestyle. The costumes and ornaments adorned by the performers tell a unique narrative that reconnects the contemporary with the ancient world. The different costumes play an important role in bringing the various characters to life whilst reinforcing the believability of the various scenes.